Beneficiation of the Nechalacho rare earth deposit. Part 2: Characterisation of products from gravity and magnetic separation. (December 2016) - Jordens, Adam; Marion, Chris; Langlois, Ray; Grammatikopoulos, Tassos; Sheridan, Richard S.; Teng, Chaoyi; Demers, Hendrix; Gauvin, Raynald; Rowson, Neil A.; Waters, Kristian E.
Highlights: Recovery of rare earth minerals from Knelson and Falcon decreases with particle size. Oversize material (>300 μm) captured by Knelson enriched with heavy REE minerals (zircon). Highest REE grade produced using Knelson and low intensity magnetic drum separator. Abstract: The application of mineral beneficiation techniques to valuable rare earth element (REE) bearing minerals requires a significant amount of research. A previous paper (Jordens et al., 2016) described a series of physical separation processes employed to pre-concentrate rare earth minerals (REM) and reject iron oxide minerals from the Nechalacho Deposit. In addition to grade and recovery information it is important to understand the performance of these separations from a mineralogical perspective. Information on liberation, mineral associations, magnetic properties and size-by-size recoveries can be used to further improve process designs for this deposit. This work employs automated mineralogy (QEMSCAN), scanning electron microscopy and a vibrating sample magnetometer to characterise the products from laboratory gravity separation (Knelson and Falcon centrifugal concentrators) and magnetic separation (varying intensity wet drum magnetic separators). The information gathered is then used to identify the optimum fraction for downstream flotation separation. The selected flowsheet included a Knelson centrifugal concentrator and low intensity drum magnetic separation resulting in a total rare earth oxide (TREO) recovery of 11.75% and a TREO grade of 7.50%.